The cost of capital - Porras, Eva R. (Palgrave Macmillan, 2011)
In this book, the relationship between risk, return and the cost of capital is contextualized by relating it to the needs of investors and borrowers, the historical evidence, and theories of choice and behavior. The text spans financial theory, its empirical tests and applications to real-world financial problems while keeping an entertaining easy-to-read style